Achieving air-stable n-type single-walled carbon nanotubes with high thermoelectric performance by doping with polyethylene glycol and N, N-dimethylferrocenemethylamine. (16th June 2023) - He, Guoliang; Nie, Xiuxiu; Cao, Guibin; Ren, Zhibo; Yang, Jing; Wu, Yufeng; Li, Anqi; Tang, Xuyan; Wu, Jiatao; Wang, Lei; Gao, Chunmei
Abstract: The development of n-type thermoelectric (TE) materials with high TE performance and long-term air stability is one of the key drivers to advance the application of TE materials today. Here, a series of single-walled carbon nanotubes (SWCNT)/N, N-dimethylferrocenemethylamine(FcMA)/polyethylene glycol (PEG) composites were fabricated using a simple solution mixing process. The high electron-donating FcMA and the strong SWCNTs-binding PEG may cause a synergistic effect. A highest power factor (600.6 μW m −1 K −2 ) of SWCNT/FcMA/PEG-5% was achieved, which is higher than that of SWCNTs/PEG (5%) (217.6 μW m −1 K −2 ) and SWCNTs/FcMA (567.5 μW m −1 K −2 ), respectively. In addition, SWCNT/FcMA/PEG-5% composites displayed long-term air-stability, the S of which remained 88% after exposed to air for over 900 h. Since the ratio of PEG is relatively low, the high air-stability is mainly not due to the coating of SWCNT surface by PEG as literature reported. Based on the results of the X-ray photophysical spectra, the high air-stability can be attributed to the stronger binding ability of PEG to the defects of SWCNTs than that of O2, which relieves the oxidation of SWCNT, thus improving the air-stability. This strategy will provide insight in the development of air-stable n-type TE materials with high TE performance. Graphical abstract: Image 1 Highlights: SWCNT/FcMA/PEG-5% exhibited the highest n-type power factor of 600.6 μW m −1 K −2 . SWCNT/FcMA/PEG-5% displayed high air stability. The S of SWCNT/FcMA/PEG-5% is about 88% preserved upon air exposure for 900 h. After exposed for 700 h, about 80% of the device open-circuit voltage remained.